Semelhança de triângulos: atividades práticas com o auxílio do geogebra - Angelin, Arlindo Moacir (2019)
In this paper we elaborate and apply a proposal of activities for students of the 9th grade of Elementary School with the objective of making the study of Geometry more attractive and significant. The contents worked were Similarity of Triangles, Tales’ Theorem and homotheties. We use similarity of triangles to solve practical problems as inaccessible height calculation. The technique used in this paper was the problem solving proposed by Polya (POLYA, 2006). In addition, we use GeoGebra software in several activities involving cases of triangle similarity. Finally, we performed a practical activity involving the classic problem of the Eupaline tunnel (RODRIGUES, 2010). The application of the proposal provided students leading situations, creating a significant increase in knowledge gained in relation to the properties studied.